2018
DOI: 10.1002/jsfa.9363
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and physicochemical properties of novel low‐phosphorus egg yolk protein

Abstract: LPYP can be effectively obtained by alkaline protease hydrolysis and subsequent alkali dephosphorization. The prepared LPYP can be considered to be a type of safe and suitable protein resource for CKD patients. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The authors observed no effect of salting treatment or high-intensity ultrasonic treatment on the protein structure of egg yolk, and similar SDS-PAGE patterns were observed before and after treatment. The secondary structure of the residual protein was measured by circular dichroism (CD) spectroscopy, and the data are displayed as the percentage of the corresponding area by ratio to the total amide I band area 28,29) . Figure 6c shows that the extraction processes caused obvious changes in the secondary structure of the residual protein.…”
Section: Effect Of Extraction Processes On the Emulsifyingmentioning
confidence: 99%
“…The authors observed no effect of salting treatment or high-intensity ultrasonic treatment on the protein structure of egg yolk, and similar SDS-PAGE patterns were observed before and after treatment. The secondary structure of the residual protein was measured by circular dichroism (CD) spectroscopy, and the data are displayed as the percentage of the corresponding area by ratio to the total amide I band area 28,29) . Figure 6c shows that the extraction processes caused obvious changes in the secondary structure of the residual protein.…”
Section: Effect Of Extraction Processes On the Emulsifyingmentioning
confidence: 99%
“…Because most of the phosphorus is contained in the yolk (586 mg/100 g), the phosphorus-to-protein ratio content of a whole egg is 13.4 mg/g compared to a more desirable ratio of 1.4 mg/g for an egg white [83]. Successful efforts have been made to prepare low phosphorus egg yolk proteins to be used in marketed egg products which provide a favorable phosphorus-to-protein ratio [33]. One small pilot study of 13 MHD (maintenance hemodialysis) patients found a significant decrease in serum phosphorus after substituting eight ounces of pasteurized liquid egg whites for meat at one meal per day over a six-week period; however, researchers acknowledged the absence of a control, lack of randomization and short duration of this study as shortcomings in drawing conclusions about employing this dietary intervention for long term phosphorus control [30].…”
Section: Phosphorus and Phosphorus-to-protein Ratiomentioning
confidence: 99%